Nationalism, fundamentalism, and democracy in Bangladesh - Jahangir, Burhanuddin Khan. (Dhaka : International Centre for Bengal Studies, 2002)
On different eras of political governance in post 1971 Bangladesh; a study.
Includes bibliographical references and index.
Keywords: Democracy -- Bangladesh; Fundamentalism -- Bangladesh; Nationalism -- Bangladesh; Bangladesh -- Politics and government -- 1971-